2010
DOI: 10.1016/j.jhydrol.2010.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Scenario-neutral approach to climate change impact studies: Application to flood risk

Abstract: This paper presents a novel framework for undertaking robust climate change impact studies, which can be used for testing the robustness of precautionary climate change allowances used in engineering design. It is illustrated with respect to fluvial flood risk in the UK. The methodology departs from conventional scenario-led impact studies because it is based on sensitivity analyses of catchment responses to a plausible range of climate changes (rather than the time-varying outcome of individual scenarios), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
294
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(311 citation statements)
references
References 36 publications
3
294
0
Order By: Relevance
“…The result was 225 series of phytoplankton populations for each of the five phytoplankton groups and each of the five reaches. These series were subsequently combined to response surfaces (Prudhomme et al, 2010) showing the variation in mean phytoplankton concentration due to climatic alterations. This allows quantifying how the phytoplankton concentration could be affected by changing climate and understanding how the dynamics of the different phytoplankton groups might evolve with climate.…”
Section: Climate Scenariosmentioning
confidence: 99%
See 3 more Smart Citations
“…The result was 225 series of phytoplankton populations for each of the five phytoplankton groups and each of the five reaches. These series were subsequently combined to response surfaces (Prudhomme et al, 2010) showing the variation in mean phytoplankton concentration due to climatic alterations. This allows quantifying how the phytoplankton concentration could be affected by changing climate and understanding how the dynamics of the different phytoplankton groups might evolve with climate.…”
Section: Climate Scenariosmentioning
confidence: 99%
“…In this study, a "bottom-up", or "scenario-neutral" approach to climate change impact assessment (Prudhomme et al, 2010) was employed to evaluate the effect of climate change on phytoplankton concentrations and composition. It consists in (i) identifying sources of climatic alteration that are likely to affect the variable object of the study, (ii) applying these possible alterations to the observed climate to produce altered climatic series (usually precipitation and/or temperature), (iii) driving a mathematical model (hydrological, water quality, water systems, eco-hydrological, phytoplankton, etc.)…”
Section: Modelling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a scenario-neutral framework was developed to assess the sensitivity of flood peaks to climate change in Britain (Prudhomme et al, 2010), using a sensitivity domain comprising 4200 combinations of changes in precipitation (P), temperature (T) and potential evapotranspiration (PE). In part 1 (Prudhomme et al, submitted)this sensitivity framework was applied to 154 catchments using hydrological modelling, resulting in flood response surfaces illustrating changes in 2-, 10-and 20-year return period flood peaks for each catchment (Prudhomme et al., submitted, Section 2.4).…”
Section: Introductionmentioning
confidence: 99%